Community-based treatment of cutaneous leishmaniasis using cryotherapy and miltefosine in Southwest Ethiopia: the way forward? - van Henten, Saskia; Pareyn, Myrthe; Tadesse, Dagimawie; Kassa, Mekidim; Techane, Mehret; Kinfe, Eyerusalem; Girma, Nigatu; Demeke, Degnet; Mesay, Mebratu; Kassa, Mekibib; Temesgen, Rodas; Shewangizaw, Misgun; et al. (Frontiers in Medicine, 2023)
Background: Cutaneous leishmaniasis (CL) is a common, yet massively underreported skin morbidity in Ethiopia. Most patients never seek treatment, as this is offered only in specialized treatment centers. Early diagnosis and treatment through decentralization is crucial to decrease transmission and to reach the NTD roadmap goals. However, little information is available on outcomes and challenges of community-based treatment initiatives.Methods: A community-based prospective cohort study was conducted in Ochollo. Patients with clinically or microscopy confirmed CL were included. Cryotherapy was (to be) given weekly with at least four sessions for uncomplicated lesions, and miltefosine was given for four weeks for complicated lesions. Miltefosine adherence was assessed by counting pill strips. Clinical and patientreported outcomes (dermatological life quality index and patient-global assessment) were assessed at month 6 (M6).Results: A total of 107 patients were included, with a median age of six years. Two patients refused, and 15 could not be treated as they were too young (<4 years) for miltefosine. Giving cryotherapy to patients weekly was not feasible due to long wound healing times and required use of topical antibiotics. Only 52.4% of miltefosine patients finished >90% of their tablets by M1. Among 46 patients treated with cryotherapy, 24 (52.2%) were cured at M6, and 9 (19.6%) had substantial improvement. Cure rate was 16/39 (41.0%) for miltefosine with 28.2% (11/39) substantial improvement. Before treatment, more than half (57.8%) of patients reported that CL did not negatively impact their life, which significantly increased to 95.2% at M6. At this time, 61.7% of patients said their lesion was clear, which was 1% before treatment.2 This is a provisional file, not the final typeset article Conclusions: Our study is the first to identify the challenges and opportunities of miltefosine and cryotherapy for community treatment of CL. Although overall cure rates were lower than expected, patient-reported outcomes were generally positive and quite some patients had good improvement.